Modification, Test and Evaluation of Manually Operated Drum Type Seeder for Lowland Paddy - Islam, Md. Syedul; Ahmad, Desa (Universiti Putra Malaysia Press, 1999)
An experiment was conducted to improve the performance of the drum type seeder developed by the International Rice Research Institute for low land paddy. The machine was evaluated and compared with the conventional hand seeding method. A seed collector assembly was designed and incorporated to the existing prototype in order to overcome the unwanted seed dropping at the headlands during turning which saved 5-7 kg of seed per hectare. Owing to the incorporation of seed collector assembly, the weight of the seeder increased by 20 percent compared to the previous prototype, but still within the capability of an average size labour.The effective field capacity of machine seeding ranged between 0.12 to 0.15 ha/hr and that of hand broadcasting was 0.22 ha/hr. The partial budget analysis revealed that by using drum type seeder and a rotary type seeder and a rotary type weeder, a farmer could earn a net benefit of US$55.06 per hectare compared to hand seedling followed by hand weeding. The break-even analysis indicated that a farmer having only 0.3 hectare of land could economically afford a drum type seeder and a rotary type weeder.